GlobalAnts: a new database on the geography of ant traits (Hymenoptera: Formicidae). Issue 1 (12th December 2016) - Parr, Catherine L.; Dunn, Robert R.; Sanders, Nathan J.; Weiser, Michael D.; Photakis, Manoli; Bishop, Tom R.; Fitzpatrick, Matthew C.; Arnan, Xavier; Baccaro, Fabricio; Brandão, Carlos R. F.; Chick, Lacy; Donoso, David A.; et al.
Abstract: In recent years the focus in ecology has shifted from species to a greater emphasis on functional traits. In tandem with this shift, a number of trait databases have been developed covering a range of taxa. Here, we introduce the GlobalAnts database. Globally, ants are dominant, diverse and provide a range of ecosystem functions. The database represents a significant tool for ecology in that it (i) contributes to a global archive of ant traits (morphology, ecology and life history) which complements existing ant databases and (ii) promotes a trait‐based approach in ant and other insect ecology through a broad set of standardised traits. The GlobalAnts database is unique in that it represents the largest online database of functional traits with associated georeferenced assemblage‐level data (abundance and/or occupancy) for any animal group with 9056 ant species and morphospecies records for entire local assemblages across 4416 sites. We describe the structure of the database, types of traits included and present a summary of data coverage. The value of the database is demonstrated through an initial examination of trait distributions across subfamilies, continents and biomes. Striking biogeographic differences in ant traits are highlighted which raise intriguing questions as to the mechanisms generating them.